2022
DOI: 10.3389/fonc.2022.822469
|View full text |Cite
|
Sign up to set email alerts
|

Application of Anlotinib Combined With Neoadjuvant Chemotherapy in Primary EWS/PNET of Lung: A Case Report

Abstract: Primary pulmonary EWS/PNET(PPES) is extremely rare and is associated with a poor prognosis. Tumor angiogenesis plays an important role in tumor, so it has become a hot topic in molecular targeted therapy. Anlotinib is a new oral small molecular multi-targeted receptor tyrosine kinase (RTK) inhibitor. This report describes a 20 year-old man with PPES. After 4 neoadjuvant chemotherapy cycles (VACwith alternating IE) combined with anlotinib, the left total pneumonectomy was performed. Then maintenance anlotinib m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…According to Dharmalingam et al [3], "Primary Ewing sarcoma of the lung is anecdotally rare, with few cases reported in the literature" until 2020. The "Ewing family of tumors" includes other tissue types, such as soft tissue origin classified as extraosseous Ewing sarcoma or primitive neuroendocrine origin [2]. Because of the rarity of extraosseous Ewing sarcomas, the therapeutic approach is the same as for osseous ones [7].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Dharmalingam et al [3], "Primary Ewing sarcoma of the lung is anecdotally rare, with few cases reported in the literature" until 2020. The "Ewing family of tumors" includes other tissue types, such as soft tissue origin classified as extraosseous Ewing sarcoma or primitive neuroendocrine origin [2]. Because of the rarity of extraosseous Ewing sarcomas, the therapeutic approach is the same as for osseous ones [7].…”
Section: Discussionmentioning
confidence: 99%
“…This kind of tumor often occurs under 25, but the congenital presentation of extraosseous Ewing sarcoma, although it is exceedingly rare, reported Haas et al (2019) [1]. Multiple loci of soft tissue Ewing sarcomas develop at multiple localization: lungs [2][3][4][5][6], liver [7], and extremely rarely, primary Ewing sarcoma occurs in the female genital organs in the uterus [8].…”
Section: Introductionmentioning
confidence: 99%
“…Extra-bone localization of ES is less frequently observed [1][2][3]. The first case of primary ES of the lung was described by Hammar et al [4] in 1989, and since then, less than 40 cases have been reported in the literature [5]. It features a distinctive immunophenotype that combines diffuse and membranous CD99 expression with FLI-1 nuclear positivity [6].…”
mentioning
confidence: 99%